APPLICATON OF MICROSEISMIC NOISE ESTIMATION IN OIL AND GAS EXPLORATION AIMED AT REDUCING ENVIRONMENTAL IMPACT - A. Yu. Tsivadze; Yu. V. Sirotinskiy; M. A. Abaturov (Юг России: экология, развитие, 2019)
Aim. This article discusses the possibility of reducing ecological costs and risks during exploration of oil and gas fields. To this end, we propose to reduce the number of exploratory drilling works performed using unjustified non‐productive wells. Such a problem can be solved with the help of innovative seismic‐acoustic methods of direct deposit exploration.Methods. The method of microseismic noise estimation (MNE) in application to hidden hydrocarbon de‐ posits is proposed. When implementing the MNE algorithms, Chebyshev spectroscopy and analysis of the noise in terms of Gaussian distribution were used.Results. The hardware im‐ plementation of the MNE method is presented. The key component of the hardware complex is presented by an autonomous microprocessor 3D seismic module. The seismic module registers signals across the frequency range of 0.5‐40 Hz with a level of spectral density of self‐noise not higher than 0.5 nm×Hz‐1/2. Presented both in land and sea design, the module is compact and mobile.Conclusion. The application of the MNE method in prospecting and exploration allows identification and exclusion of obviously non‐productive wells from drilling, as well as reduc‐ tion of the total number of wells more than by twofold. For the Caspian region, this indicator is expected to be higher. As a result, the method will provide a significant reduction in the envi‐ ronmental consequences of the oil and gas industry as a whole.